Brain tumours in the time of COVID-19: An online survey on patients’ disease experience in one Italian region - Abete-Fornara, Giorgia; Mameli, Francesca; Ruggiero, Fabiana; Meessen, Jennifer; Blanda, Adriana; Ampollini, Antonella; Locatelli, Marco; Salmaggi, Andrea; Di Cristofori, Andrea; Mauri, Ilaria; Caroli, Manuela (Frontiers in Oncology, 2023)
BACKGROUND: since the outbreak in 2019 of the COVID-19, the world has experienced an evident change in daily habits, also due to the exceptional social restrictions and health measures adopted to contain it. All these measures strongly affected not only people's daily life and psychological well-being, but also the possibility for the healthcare system to function properly. In this setting, brain tumour patients are at risk due to their higher physical and mental fragility and their need of regular care. Aim of the present study was to assess, through a self-reported online questionnaire, the patients' perception regarding their disease experience. MATHERIALS AND METHODS: we developed an anonymous self-report online survey to assess patients' disease experience during the pandemic period; we investigated the impact of the COVID-19 on patients' cancer care schedules, their psychological distress and emotions felt during the pandemic, their level of worry towards the COVID-19 and to their oncological condition. RESULTS: 107 patients answered our survey, most of them suffering from a glioma. Less than one third of the sample had appointments cancelled or delayed due to the pandemic, or converted into online visits. The 95% declared to be satisfied about their Institute oncological management. The most frequent emotions reported were peacefulness and anxiety/worry, with high levels of sense of loneliness felt by the majority of the sample, with a tendency to increase with age; the psychological distress turned out to be correlated with age and having a recurrence. Half of the sample declared a severe worry towards the oncological condition, in particular for those with a recurrence or were receiving adjuvant therapies. Moreover, recurrence patients tended to feel higher levels of worry toward the possibility to contract the COVID-19 and its effects. CONCLUSION: Our results describe how fragile and needing patients with a brain tumour may be, especially those with more severe clinical conditions. These data may contribute to increase healthcare professionals' knowledge about brain tumour patients' needs and fears, in order to offer them a better hospital experience and to improve their clinical management and, possibly, to decrease the psychological burden of patients and their families.